Meta-Analysis the Effect of Family-Based Intervention in Increasing Quality of Life in Diabetes Mellitus Patients - Novita Herlita Dewi; Didik Gunawan Tamtomo; Rita Benya Adriani (Journal of Health Promotion and Behavior, 2021)
Background: An increase in type 2 diabetes and related risk factors, which include increased rates of obesity, an unhealthy diet, and a lack of physical activity. One category of intervention to prevent diabetes in adults that has developed rapidly in recent years is family-based intervention. The family is also the party that helps each member in maintaining health, such as meeting the needs of eating, drinking, bathing, resting, recreation, sports, and others. This study aims to estimate the magnitude of the effect of family-based intervention on improving the quality of life of patients with diabetes mellitus.Subjects and Method: This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: PubMed, Science Direct, Google Schoolar and SpingerLink by selecting articles published in 2010-2020. The PICOs of this study are, Population: diabetes mellitus patients, Intervention: family-based intervention, Comparison: not family-based intervention, Outcome: quality of life. The keywords used are “family-based intervention” OR “family-based program” OR “family-based treatment” OR “family-based” OR “home-based intervention” OR “household-based intervention” AND “quality of life” AND “diabetes mellitus” AND RCT OR “randomized controlled trial” OR “cluster-randomized controlled trial. The inclusion criteria were full paper articles with Randomized Controlled Trial (RCT) research methods, the measure of the relationship used was Mean SD, the intervention given was family-based intervention, the research subjects were patients with diabetes mellitus. Eligible articles were analyzed using the Revman 5.3 application.Results: A meta-analysis of 10 articles showed the results of Family-Based Intervention (SMD 0.23; 95% CI= -0.08 to 0.53; p=0.140).Conclusion: Family-Based Intervention has an effect on improving the quality of life of patients with diabetes mellitus.Keywords: family-based intervention, quality of life, diabetes mellitus, Meta-AnalysisCorrespondence:Novita Herlita Dewi. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: dnovitaherlita@gmai.com Mobile: 081311426454Journal of Health Promotion and Behavior (2021), 06(03): 212-223DOI: https://doi.org/10.26911/thejhpb.2021.06.03.05